LATAR DALAM NOVEL KURA-KURA BERJANGGUT KARYA AZHARI AIYUB - Muhammad Iqbal; Nurul Akmal; Latifah Hanum (TELAGA BAHASA, 2021)
The Novel Kura-Kura Berjanggut by Azhari Aiyub depicts a setting that can be used as knowledge related to life in ancient times such as place, time and social, and life lessons.The purpose of this research is to describe the setting of the novel Kura-Kura Berjanggut by Azhari Aiyub. The method used is the descriptive qualitative approach. The research data source is the Novel Kura-Kura Berjanggut by Azhari Aiyub.  This research is text, phrases, and sentences about the setting of the Novel Kura-Kura Berjanggut by Azhari Aiyub. Data collection techniques used are library or literature study techniques. Data analysis was performed using descriptive qualitative analysis techniques. This research results showed that were containof three setting in the Novel Kura-Kura Berjanggut by Azhari Aiyub. First, the most dominant setting is in Teluk Lamuri and Istana Darud Dunya. second, the setting time setting described in the novel without dating and describing the situation. Third, the social setting dominated the typed of attitude and habits to life. Keywords: Intrinsic Element, Setting, Novel                                                   Abstrak Novel Kura-Kura Berjanggut karya Azhari Aiyub menggambarkan latar yang dapat dijadikan sebagai pengetahuan terkait kehidupan di masa zaman dahulu seperti tempat, waktu dan sosial, serta pelajaran hidup. Tujuan penelitian ini adalah mendeskripsikan unsur latar yang terdapat di dalam Novel Kura-Kura Berjanggut karya Azhari Aiyub. Metode yang digunakan adalah deskriptif dengan pendekatan kualitatif. Sumber data penelitian ini Novel Kura-Kura Berjanggut karya Azhari Aiyub. Data penelitian ini adalah teks berupa kata, frasa, dan kalimat tentang latar yang terdapat dalam Novel Kura-Kura Berjanggut karya Azhari Aiyub. Teknik pengumpulan data yang digunakan adalah teknik pustaka atau studi kepustakaan. Analisis data dilakukan dengan teknik analisis kualitatif deskriptif. Hasil penelitian ini menunjukkan bahwa terkandung tiga jenis unsur latar dalam Novel Kura-Kura Berjanggut karya Azhari Aiyub. Pertama, latar tempat yang paling dominan terdapat di Teluk Lamuri dan Istana Darud Dunya. Kedua, latar waktu digambarkan dalam novel tersebut berupa penanggalan dan penggambaran situasi. Ketiga, latar sosial yang mendominasi berjenis kebiasaan hidup dan bersikap.  The Novel Kura-Kura Berjanggut by Azhari Aiyub depicts a setting that can be used as knowledge related to life in ancient times such as place, time and social, and life lessons. The purpose of this reasearches are to described the setting of the novel Kura-Kura Berjanggut by Azhari Aiyub. The method used is descriptive qualitative approach. The research data source is the Novel Kura-Kura Berjanggut by Azhari Aiyub.  This research are text, phrass and the sentence about the setting of the Novel Kura-Kura Berjanggut by Azhari Aiyub. Data collection techniques used are library or literature study techniques. Data analysis was performed using descriptive qualitative analysis techniques. This research results showed that were containof three setting in the Novel Kura-Kura Berjanggut by Azhari Aiyub. First, the most dominant setting is in Teluk Lamuri and Istana Darud Dunya. second, the setting time setting described in the novel without dating and describing the situation. Third, the social setting  that dominated the typed of attitude and habits to life.